Performance Analysis of Digital Tourism Promotion Services Through the Ayo Piknik (APIK) Platform in Klaten Regency: Analisis Kinerja Layanan Promosi Pariwisata Digital Melalui Platform Ayo Piknik (APIK) di Kabupaten Klaten - Yoldananda Prasotya Widarto; Ferri Wicaksono (Jurnal Pemerintahan dan Politik, 2026)
Purpose: This study aims to analyze the performance of digital tourism promotion services through the Ayo Piknik Klaten (APIK) platform in Klaten Regency using the e-government success theory, which includes support, capacity, and value, as well as the public value theory to find out the public value generated from the implementation of the platform. Methodology: The research used a qualitative approach with descriptive methods. Data collection was conducted through in-depth interviews, observation, documentation, and document analysis. Findings: The results of the study show that the value element has succeeded in creating public value through an increase in tourist visits, an increase in the tourism sector's Local Own-Source Revenue by 14.81% in the 2024-2025 period, as well as social, cultural, and political values. These achievements are supported by support elements in the form of government commitment, budget support, and adequate regulations, as well as capacity elements in the form of good technological infrastructure and human resources, although socialization and handling of technical obstacles still need to be improved. Practical Implication: This research can serve as a reference for the Klaten Regency Government in optimizing the APIK platform through strengthening socialization, updating information, increasing technological capacity, and strengthening collaboration to support more effective digital tourism promotion services. Originality: This study examines the performance of local government digital tourism promotion services using a combination of E-Government Success Theory and Public Value Theory, which are still limited in the literature.